Post a New Question

calculus

posted by .

simplify 6x^4-2xy^4 divided by 2xy

  • calculus -

    3x^3/y - y^3

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Algebra

    Simplify (2xy^2+3)((2xy^2)^2-(2xy^2)(3)+(3)^2) This reminds me of (U+a)(U^2- aU + a^2). When mulipltiplied out, one gets a cubic equation. Do you remember the formula for factoring the sum of two cubes?
  2. Math

    Can 2xy - y - 1 be factored out? How? about all you can do is take the common y out of the first two terms; that in itself is not much help. dont know if this is rite or not..but just a guess.. assuming 2xy - y - 1 = 0 2xy - y = 1
  3. Calculus

    Consider the equation: x^2 - 2xy + 4y^2 = 64 Write an expression of the slope of the curve at any point. (y^p)= y prime My work 2x - 2(xy^p + y) + 8yy^p = 0 2x -2xy^p - 2y + 8yy^p = 0 -2xy^p + 8yy^p = 2y -2x factored out y^p and then …
  4. calculus

    The equation x^2 y+2xy^3=8defines y as a function of x,y=f(x), near x=2, y=1. a) Find dy/dx. b) Now, find the slope of the curve x^2y+2xy^3=8 when x=2, y=1.
  5. Calculus

    I am having trouble differentiating x^2 + 2lny = y (solving for dy/dx). I know that I need to do implicit differentiation, but the answer I get is not correct. The answer I got was (2x-2xy)/2, but the answer is (2xy)/(y-2). How do …
  6. Algebra

    I thought number 4 on this list was incorrect but didn't know how to fully explain it here is the list that I have. Please look at the following simplification of an algebraic expression. Which line contains the mistake and why?
  7. Algebra

    Please look at the following simplification of an algebraic expression. Which line contains the mistake and why?
  8. pre-cal

    Use Pascal's triangle to expand the expression. (x − y)5 so I tried to work this out: (x-y)^5 = [(x-y)(x-y)][(x-y)(x-y)](x-y) (x-y)^2 = (x-y)(x-y) = x^2 - 2xy + y^2 x^2 - 2xy + y^2)(x^2 - 2xy + y^2) = x^4 -4x^3y + 6x^2y^2 - 4xy^3 …
  9. Calculus

    Find y" by implicit differentiation. x^3+y^3 = 1 (x^3)'+(y^3)' = (1)' 3x^2+3y^2(y') = 0 3y^2(y') = -3x^2 y' = -3x^2/3y^2 y' = -x^2/y^2 y" = [(y^2)(-x^2)'-(-x^2)(y^2)']/y^4 y" = [(y^2)(-2x)-(-x^2)(2y)]/y^4 y" = [(-2xy^2)-(-2yx^2)]/y^4 …
  10. simultaneous equation

    x^2+y^2-2xy=21 x^2+2xy-8y^2=0 find x and y help me plz

More Similar Questions

Post a New Question